What is wrong with yarrow in Kazakhstan and Central Asia - A. N. Kuprijanov; Yu. E. Kulemin (Проблемы ботаники Южной Сибири и Монголии, 2021)
Data on the distribution of the genus Achillea L. (A. asiatica Serg., Achillea x kasakhstanica Kupr. Et Alibekov, Achillea setacea Waldst. Et Kit., Achillea kamelinii Kupr., Achillea karatavica R. Kam., A. sergievskiana Schaulo et Schwe. , A. stepposa Klok. Et Krytzka, Achillea tianschanica Kupr. Et Kulemin) in Kazakhstan. In the course of the work, the available materials of Herbariums LE, AA, MW, TK, MHA, TASH, KUZ, KG were critically revised, which allowed us to identify morphological differences, peculiar ecological conditions of growth and characteristic areas. The morphological differences of closely related species and the differences obtained from the analysis of ISSR-PCR data are shown.